The influence of size, financial leverage, and age on financial performance: A study of gasoline firms on the Vietnamese stock market - Dung, Vu Quoc; Anh, Le The; Hieu, Pham Van; Hau, Nguyen Van; Trang, To Thi Thu (Edelweiss Applied Science and Technology, 2026)
The purpose of this research is to investigate the impact of firm size, financial leverage, and firm age on the financial performance, measured by return on assets (ROA), of listed gasoline enterprises on the Vietnamese stock market. The research methods primarily used were quantitative. The research sample consists of 20 listed gasoline firms observed over the period 2021–2024, employing a combination of qualitative and quantitative research methods. A regression model was developed to examine the relationships between the explanatory variables and ROA, while ensuring the validity of key linear regression assumptions. The empirical results reveal that financial leverage (Lev) has a positive and statistically significant effect on ROA, with a coefficient of 0.1569723, indicating that an appropriate use of debt can enhance financial performance in gasoline firms. In contrast, firm age (Age) exhibits a negative relationship with ROA, with a coefficient of –0.0008917, suggesting that older firms may face challenges related to organizational rigidity and reduced adaptability in a dynamic market environment. Notably, firm size (Size) does not show a statistically significant impact on ROA, implying that scale advantages are not a decisive factor for financial performance in the gasoline industry during the study period. The findings provide valuable empirical evidence for corporate managers, investors, and policymakers in designing financial strategies and improving the business performance of listed gasoline enterprises in Vietnam.